Application of the law in time. Regarding Act N° 29057 - Arriola Espino, Marcela (2008)
From the position assumed by our procedural legal ordering on the immediate application of the norm, even to the process in proceeding, it indicates that this one enters in use, or it's official the day after its publication, so that the acts that arise from its validity are under its frame of application. However, the procedural norm is applied immediately for processes that are initiated, even for the ones that are in process, but the rules of competition, the interposed impugning means, the procedural acts with execution principle and the terms that will have begun, will continue being treated by the previous norm.